Importance of Tetramer Formation by the Nitrogen Assimilation Control Protein for Strong Repression of Glutamate Dehydrogenase Formation in Klebsiella pneumoniae - Rosario, Christopher J. (American Society for Microbiology, 2005)
The nitrogen assimilation control protein (NAC) from Klebsiella pneumoniae is a very versatile regulatory protein. NAC activates transcription of operons such as hut (histidine utilization) and ure (urea utilization), whose products generate ammonia. NAC also represses the transcription of genes such as gdhA, whose products use ammonia. NAC exerts a weak repression at gdhA by competing with the binding of a lysine-sensitive activator. NAC also strongly represses transcription of gdhA (about 20-fold) by binding to two separated sites, suggesting a model involving DNA looping. We have identified negative control mutants that are unable to exert this strong repression of gdhA expression but still activate hut and ure expression normally. Some of these negative control mutants (e.g., NAC(86ter) and NAC(132ter)) delete the C-terminal domain, thought to be required for tetramerization. Other negative control mutants (e.g., NAC(L111K) and NAC(L125R)) alter single amino acids involved in tetramerization. In this work we used gel filtration to show that NAC(86ter) and NAC(L111K) are dimers in solution, even at high concentration (NAC(WT) is a tetramer). Moreover, using a combination of DNase I footprints and gel mobility shifts assays, we showed that when NAC(WT) binds to two adjacent sites on a DNA fragment, NAC(WT) binds as a tetramer that bends the DNA fragment significantly. NAC(L111K) binds to such a fragment as two independent dimers without inducing the strong bend. Thus, NAC(L111K) is a dimer in solution or when bound to DNA. NAC(L111K) (typical of the negative control mutants) is wild type for every other property tested: (i) it activates transcription at hut and ure; (ii) it competes with the lysine-sensitive activator for binding at gdhA; (iii) it binds to the same sites at the hut, ure, nac, and gdhA promoters as NAC(WT); (iv) the relative affinity of NAC(L111K) for these sites follows the same order as NAC(WT) (ure > gdhA > nac > hut); (v) it induces the same slight bend as dimers of NAC(WT); and (vi) its DNase I footprints at these sites are indistinguishable from those of NAC(WT) (except for features ascribed to tetramer formation). The only two phenotypes we know for negative control mutants of NAC are their inability to tetramerize and their inability to cause the strong repression of gdhA. Thus, we propose that in order for NAC(WT) to exert the strong repression, it must form a tetramer that bridges the two sites at gdhA (similar to other DNA looping models) and that the negative control mutants of NAC, which fail to tetramerize, cannot form this loop and thus fail to exert the strong repression at gdhA.